THE UTILIZATION OF MOBILE-HEALTH INTERVENTION IN IMPROVING TREATMENT COMPLIANCE BEHAVIOR IN TUBERCULOSIS PATIENTS - Eko Budi Laksono; Andrew Johan; Meira Erawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Mobile-health assists health workers in monitoring and observing patient compliance behavior during TB treatment. Objectives: The purpose of this review is to identify the use of mobile-health interventions in improving medication compliance behavior in tuberculosis patients. Design: This research was conducted by following the scoping framework. Data Sources: This study was conducted following a scoping review framework. This research literature search relied on data from PubMed, Scopus, and Science Direct databases. Using the keywords “mobile application”, “Directly-Observed Treatment Short-course (DOTS)”, “medication adherence”, “tuberculosis patients”, and “mobile-health”. This scoping review uses data from 10 articles published between 2010-2019. Utilization of Mobile-Health in improving drug adherence of TB patients. Review Methods: The particle screening method was used for the review and was guided by the PRISMA diagram. As well as an analysis of the articles reviewed. Results: The m-health intervention has a positive impact on TB treatment. The benefits of m-health are increasing patient knowledge, providing social support, providing motivational support and increasing patient compliance behavior during treatment. The m-health application contains features such as short message service (SMS), video, telephone, and picture messages. Conclusion: Mobile-health interventions can be applied independently with counseling, motivation and health education in improving medication compliance behavior. The advantages of mobile-health are that patients become more open, it saves time and distance, and also it strengthens communication between nurses and patients.